1984
DOI: 10.1017/s0022149x00028716
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical localization of phosphomonoesterases in Avhellina lahorea Woodland, 1927 (Cestoda: Anoplocephalida)

Abstract: Non-specific and specific phosphatases have been histochemically localized in the tissues of Avitellina lahorea, an intestinal parasite of sheep and goats. Large quantities of acid phosphatase, alkaline phosphatase and adenosine triphosphatase were observed in almost all organs except the parenchyma where there were moderate amounts of acid phosphatase and no alkaline phosphatase; the reproductive ducts contained moderate amounts of alkaline phosphatase. 5-nucleotidase was observed only in the uterus, egg pouc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
4
3
0
Order By: Relevance
“…The presence of alkaline phosphatases has been observed in excretory canals of Moniezia expansa. This is in accordance to Erasmus (1957), Bogitsh (1963, Lee and Tatchell (1964), Mayberry andTibbitts (1972), Sircar andSinha (1978), Roy (1979) and Farooq and Farooqi (1984) in different cestodes. But the absence of acid phosphatase in excretory canal in M.expansa in present study by author was different from that of Roy (1979) and Farooq and Farooqi (1984) who reported acid phosphatase in the excretory canals of Raillietina (R.) johri and Avitellina lahorea respectively.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The presence of alkaline phosphatases has been observed in excretory canals of Moniezia expansa. This is in accordance to Erasmus (1957), Bogitsh (1963, Lee and Tatchell (1964), Mayberry andTibbitts (1972), Sircar andSinha (1978), Roy (1979) and Farooq and Farooqi (1984) in different cestodes. But the absence of acid phosphatase in excretory canal in M.expansa in present study by author was different from that of Roy (1979) and Farooq and Farooqi (1984) who reported acid phosphatase in the excretory canals of Raillietina (R.) johri and Avitellina lahorea respectively.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, both acid and alkaline phosphatases have been observed in the tegument of Moniezia expansa. These are in accordance to that of Erasmus (1957b), Howells and Erasmus (1969), Khera andArora (1984), Varma et al (1985) in Moniezia expansa and Erasmus (1957b), Waitz (1963), Bogitsh (1963, Waitz and Schardein (1964), Roy (1979), Farooq andFarooqi (1984), Varma et al (1985), Upender and Bhargavi (1985) and Suman et. al.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations